Female Body as a Site of Revenge: Understanding the Predicament of Deshpande’s “A Liberated Woman” at the Intersection of Class and Gender - Sharma, Nancy (SARE: Southeast Asian Review of English, 2024)
Shashi Deshpande, an acclaimed Indian writer, is famous for tapping into the vocabularies and perceptions made available by the growth of the middle class in India. Throughout the years, Deshpande has emphasised the struggles of middle-class women at the intersection of Capitalism and patriarchy. Capitalist patriarchy represents ‘the dialectical relation between capitalist class structure and hierarchical sexual structure’ and can be considered the real cause of women’s oppression in contemporary times. (Eisenstein, Capitalist Patriarchy 5). Deshpande’s “A Liberated Woman” establishes an innate relationship between an educated middle-class working woman’s “inner” life and social praxis. The text explores the protagonist’s struggle to gain autonomy within the institution of marriage and motherhood and further attempts to analyze how the so-called transgression of middle-class women into the public space disturbs the harmony of family life and supposed marital bliss. Even after being subject to sadism, Deshpande’s woman refuses to acknowledge the gravity and intricacies of the sexual assault as she tries to mystify the concrete bruises visible on her body. The present paper attempts to understand Deshpande’s unnamed protagonist’s predicament at the intersection of class and gender by drawing insights from the discourse concerning Capitalist patriarchy and the idea of intersectionality. It highlights how the plight of Deshpande’s woman can only be understood holistically when analyzed through an intersectional lens that considers her position vis-à-vis the economic, sociocultural, legal, and political domains in India. It further endeavors to disentangle how the female body of the unnamed protagonist of Deshpande’s oeuvre acts as a ‘site’ of control and domination by undertaking a close textual analysis of the text.